THE MIXED GENETIC SCHEME OF NATURAL HYDROCARBON SYNTHESIS: A PRINCIPLE MODEL - Abidov A.A.; Dolgopolov F.G. (My University, 2004)
The development of the mixed genetic scheme of the natural HC synthesis on the basis of the factual material from five petroliferous regions in Uzbekistan has shown that the proposed method may be applied to other petroliferous provinces of the world without any restriction. In applied terms, this leads to the reappraisal of their resources and determination of new strategic targets for geological exploration.